Learning MS dynamics AX 2012 programming : develop and customize your very own Microsoft Dynamics AX solution quickly and efficiently /: develop and customize your very own Microsoft Dynamics AX solution quickly and efficiently. (2014) - Rasheed, Mohammed; Dalen, Erlend
No abstract available